Optical Properties of Al-and Mo-Doped and Codoped ZnO Films Deposited by Sol-Gel Process - He, Hai-Yan (Recent Patents on Materials Science, 2014)
Enhancing the optical transmission of ZnO film is an important topic for its application. This work presents the manufacture and potential application of the ZnO materials containing various dopants in recent literatures and patents and then focuses on the comparison of optical properties of Al- and Mo-doped and codoped ZnO films. The films were deposited on quartz glass substrate by a sol-gel process, and characterized by X-ray diffraction, atomic force microscopy, atomic force microscopy, and UV-vis and luminescent spectrophotometries. The Mo-doping was more effective in increasing transmission and widening band gap than the Al-doping, while the codoping was more effective than single dopings. The films also showed strong ultraviolet, violet and bluish violet emission.
Keywords: doping